PROGRESSIVE MULTIFOCAL LEUCOENCEPHALOPATHY: AN ATYPICAL CASE. Issue 11 (14th October 2015) - Maxwell, Alice; Archer, Hilary; Cohen, Nicki; Love, Seth; Cottrell, David
Abstract : Case report: A 71 year old man presented with a three month history of gradual arm and leg weakness, followed by neck stiffness, dysphagia, dysarthria and hypophonia. Past Medical History included Burkitt's lymphoma of the jaw 14 years previously, treated with chemotherapy and radiotherapy. Examination demonstrated a restriction of upgaze and dysphonia. Tone was markedly increased, and power reduced globally at a grading of 4/5. Reflexes were brisk with an upgoing left plantar. Investigations revealed, longstanding idiopathic lymphopenia for 10 years, CT chest/abdominal/pelvis was normal, serial MRI of the brain demonstrated changes in the subcortical white matter, frontal and parietal lobes. JC virus PCR was negative, however, brain biopsy was consistent with Progressive Multifocal Leucoencephalopathy (PML). Discussion: PML is caused by reactivation of the polyomavirus JC in the CNS. Reactivation typically occurs following immunosuppression e.g. HIV, haematological malignancies and drugs. Gold standard for diagnosis is brain biopsy as JC virus PCR has a sensitivity of only 80%. Treatment is through removal of the immunosuppressive agent, and immune reconstitution. PML should be considered in all patients with a suggestive clinical and radiological presentation where there is current or historical immunosuppression, should JC virus PCR be negative a tissue biopsy should be sought.